2021
DOI: 10.1017/s1047951121000524
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with a lower chance of having gaps in care in adult congenital heart disease

Abstract: Background: To promote good health in patients with congenital heart disease (CHD), prevention of gaps in care is essential, as adverse prognosis is associated with care gaps. A well-organised, formal transition programme may help prevent loss to follow up after leaving paediatric care. To inform the development of a transition programme, we investigated factors associated with care gaps in adults with CHD. Methods: Between 15 October 2018 and 15 November 2019 data on patient characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…24,29 It is not uncommon for some adolescents and ACHD patients to be unaware of the need for long-term follow-up especially if they remain asymptomatic. 13,19,33,34 Transition programs from the outset need to ensure that patients understand the importance of follow-up and the ramifications of lapses in care. Notably, Ko et al found that by simply emphasizing the importance of receiving ongoing care into adulthood, patients were 70% less likely to experience a lapse in care.…”
Section: Results and Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…24,29 It is not uncommon for some adolescents and ACHD patients to be unaware of the need for long-term follow-up especially if they remain asymptomatic. 13,19,33,34 Transition programs from the outset need to ensure that patients understand the importance of follow-up and the ramifications of lapses in care. Notably, Ko et al found that by simply emphasizing the importance of receiving ongoing care into adulthood, patients were 70% less likely to experience a lapse in care.…”
Section: Results and Commentsmentioning
confidence: 99%
“…Notably, Ko et al found that by simply emphasizing the importance of receiving ongoing care into adulthood, patients were 70% less likely to experience a lapse in care. 33…”
Section: Results and Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in clinical management and a substantial decrease in mortality, CHD patients continue to face significant morbidity and poor long-term outcomes associated with GIC. 26 Recognized as an independent predictor of mortality, GIC are 3 times more likely to lead to urgent interventions, patients receiving a new cardiac diagnosis, and patients presenting symptomatically. 26 Our analysis reveals that GIC in certain subpopulations are ongoing and increasing.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recognized as an independent predictor of mortality, GIC are 3 times more likely to lead to urgent interventions, patients receiving a new cardiac diagnosis, and patients presenting symptomatically. 26 Our analysis reveals that GIC in certain subpopulations are ongoing and increasing. In the absence of interventions that proactively incorporate or focus specifically on SDOH factors in susceptible subpopulations of CHD patients, the trajectory of these unfavorable outcomes is unlikely to be reversed.…”
Section: Discussionmentioning
confidence: 99%